2016
DOI: 10.1186/s12935-016-0356-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DBCCR1-003 regulate the expression of DBCCR1 via DNMT1 in bladder cancer

Abstract: BackgroundMany long non coding RNAs have been identified as key modulators in cancer development. A lncRNA, DBCCR1-003, derived from the locus of tumor suppressor gene DBCCR1 (deleted in bladder cancer chromosome region 1), has unknown function. In the present study, we explored function and molecular mechanism of DBCCR1-003 in bladder cancer (BC) development.MethodsWe evaluated the expression levels of DBCCR1-003 in tissues and cells with western blot and quantitative real-time polymerase chain reaction. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…found a correlation between low DBCCR1 level and high expression of DNMT1 in bladder cancer tissues. Their data support a direct inhibition of DBCCR1 through the DNMT1-mediated methylation of DBCCR1 promoter, which can be prevented by a long non-coding RNA derived from the DBCCR1 locus itself [30]. Complementary to these findings, the results of our study implied that DBCCR1 suppression and DNMT1 activation could be synergistically induced during tumor progression via positive feed-forward mechanisms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…found a correlation between low DBCCR1 level and high expression of DNMT1 in bladder cancer tissues. Their data support a direct inhibition of DBCCR1 through the DNMT1-mediated methylation of DBCCR1 promoter, which can be prevented by a long non-coding RNA derived from the DBCCR1 locus itself [30]. Complementary to these findings, the results of our study implied that DBCCR1 suppression and DNMT1 activation could be synergistically induced during tumor progression via positive feed-forward mechanisms.…”
Section: Discussionsupporting
confidence: 85%
“…Previously, DBCCR1 has been only suggested as a potential target of DNMT1-dependent methylation during development [29]. In a most recent report [30], the gene locus of DBCCR1 has been associated with DNMT1 activity in cancer. In this study, Qi D et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, zebularine increased radiation-induced DNA damage in bladder cancer cells and increased the radiation-induced tumor growth delay in a xenograft mouse model [76]. The function of DNMT1 in bladder cancer cell lines was recently discovered to be mediated by the long non-coding (lnc) RNA DBCCR1–003 derived from the locus of DBCCR1 tumor suppressor gene [77]. Habuchi et al previously demonstrated a role of the loss of DBCCR1 expression in transitional-cell bladder cancer [78].…”
Section: Targeting Dnmts In Genitourinary Cancermentioning
confidence: 99%
“…Habuchi et al previously demonstrated a role of the loss of DBCCR1 expression in transitional-cell bladder cancer [78]. Qi et al [77] reported that DBCCR1–003 normally binds to DNMT1 and prevents the hypermethylation of DBCCR1 , thus allowing its expression. Treatment with decitabine or overexpression of DBCCR1–003 resulted into increased expression of DBCCR1 via reversed promoter hypermethylation and DNMT1 binding to DBCCR1–003 and promoter DBCCR1 in the T24 bladder cancer cell line.…”
Section: Targeting Dnmts In Genitourinary Cancermentioning
confidence: 99%
See 1 more Smart Citation